The role of green tariffs in environmental harmonization - Alireza Naghavi (University College Dublin, Department of Economics, 2004)
This paper investigates the link between trade and environment by exploring the effects of green tariffs on the location of firms, innovation and environmental policy. Besides the standard effect of reducing trade and production of dirty goods, green tariffs discourage firms from relocating to pollution havens and induce them to engage in pollution abatement R&D instead. With no concern about pollution among Southern residents, green tariffs can block delocation to serve as the only means of persuading the South to harmonize its environmental standards. When some concern exists, tougher environmental regulations are adopted for a wider range of standards.
hdl:10197/1282
Keywords: F13; F18; F23; H23; Q21; R38; 330; environmental standards; eco-dumping; multinationals; location of firms; pollution abatement R&D; WTO; green tariffs